# What are the solutions to m^{2} - 9 = 0?

m = -9 and m = 0, m = -3 and m = 3, m = -3, m = 9

**Solution:**

Given equation is m^{2} - 9 = 0

=> m^{2} = 9

=> Applying square root on both sides

=> √m^{2} = √9

=> m = √(3)(3)

=> m = (±)3

Aliter:

m^{2} - 9 is the difference of squares and a^{2}-b^{2} = (a+b) (a-b)

m^{2} - 9 = (m+3)(m-3)

Given equation is m^{2} - 9 = 0

Thus (m+3)(m-3) = 0

m+3 = 0 and m-3 = 0

Thus m = 3, -3

=> **∴** m = 3 and m = -3 (Ans)

## What are the solutions to m^{2} - 9 = 0? m = -9 and m = 0, m = -3 and m = 3, m = -3, m = 9

**Summary:**

The solutions to the equation m^{2} - 9 = 0 are m = 3 and m = -3.

Math worksheets and

visual curriculum

visual curriculum